26.4k views
3 votes
Solve 4x + 1 = 3 – 2x

2 Answers

5 votes

Answer:

x=1/3

Explanation:

4x+1=3-2x

Add 2x to both sides

6x+1=3

Subtract 1 on both sides

6x=2

x=2/6

User Michaelxor
by
6.1k points
3 votes

Answer:

x = 1/3

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define equation

4x + 1 = 3 - 2x

Step 2: Solve for x

  1. Add 2x on both sides: 6x + 1 = 3
  2. Subtract 1 on both sides: 6x = 2
  3. Divide 6 on both sides: x = 1/3

Step 3: Check

Plug in x to verify it's a solution.

  1. Substitute: 4(1/3) + 1 = 3 - 2(1/3)
  2. Multiply: 4/3 + 1 = 3 - 2/3
  3. Add/Subtract: 7/3 = 7/3

Here we see that 7/3 does indeed equal 7/3.

∴ x = 1/3 is a solution of the equation.

User Zlata
by
6.0k points